Flexural performance of concrete beams internally reinforced with steel, geogrid and GFRP meshes - Aliaa K. Hanan; Majid D. Muttashar; Sallal R. Abid; Ahmed M. Yosri; Fahad Alsharari; Ahmed farouk Deifalla (Journal of Materials Research and Technology, 2023)
The focus of this study is to evaluate the internal reinforcement effect using different material meshes on the flexural capacity of concrete beams. For this purpose, eleven experimental reinforced concrete beams were tested under four-point bending. The beams were all made of normal concrete with a 150 × 200 mm2 rectangular cross-section and a length of 1200 mm. The conventional flexure and shear steel bar reinforcements were identical for the eleven beams. The reference beam was made without any internal mesh reinforcement, while the rest ten beams were reinforced with three different types of mesh materials, which were incorporated in different numbers of layers and different configurations. The used meshes were steel, geogrid and glass-fiber reinforced polymer (GFRP). One beam with U-shape mesh was made from each material, with the mesh wrapping the stirrups and extending vertically for 50 mm. In the experimental program, failure mode, load-deflection relationship, load capacity and ductility were the main characteristics that have been investigated. The test results showed that the percentage increase in the failure load capacity of the composite beams was approximately 3–25% compared to the reference beam. Furthermore, the beams with U-shape mesh configuration exhibited 17% increase in the load capacity comparing with their straight mesh counterparts. Similarly, the ductility index showed higher percentage improvement approximately 82–136% when layer number increased from 1 to 3 layers.